Effects of guide vane shape on the performances of pump-turbine: A comparative study in energy storage and power generation. (September 2022) - Lu, Zhaoheng; Tao, Ran; Yao, Zhifeng; Liu, Weichao; Xiao, Ruofu
Abstract: Pumped storage unit is a typical energy storage system in electric power grid system. Flow energy dissipation (FED) is a key factor affecting energy utilization efficiency. Guide vane has an important influence on the hydraulic performance and system stability. This study compares the FED difference of two typical guide vanes in turbine mode and pump mode based on Computational Fluid Dynamics (CFD) and entropy production method. The results show that at the same head, the flow rates in energy storage and power generation are different. In pump mode, FED concentrates in runner, guide vane, stay vane and volute. FED concentrates in runner and draft tube in turbine mode. The sources of FED in pump mode and turbine mode are different, including flow separation, jet wake, wall loss, vortex rope and back-flow. Guide vane with oval leading edge can better enhance the flow rate compared with that with sharp leading edge in turbine mode, which decreases FED at small flow rate condition by improving the matching of blade profiles and flow direction. This paper provides a reference for improving the performance of pump turbine through design.